The influence of temperature on life history traits in the Iberian slug, Arion lusitanicus. (22nd November 2012) - Slotsbo, S.; Damgaard, C.; Hansen, L.M.; Holmstrup, M.
Abstract The slug Arion lusitanicus is an invasive species which has recently become established in many European countries and is considered a serious pest, both in agriculture and private gardens. The effect of temperature on growth rate, survival, egg developmental time and hatchability of the slug are reported. The growth rate was positively correlated with temperatures up to 20°C and A. lusitanicus continued (on average) to grow until they die. A model describing how growth depends on temperature was developed, and a field survey found that the predicted growth matched the observed with reasonable accuracy. This study confirms the assumption that A. lusitanicus die after egg laying. Free‐ranging A. lusitanicus has an annual life cycle, but our data show that slugs also possess the ability to live for up to 3 years. The egg developmental time was, like growth, positively correlated with temperature and was shortest at 20°C, but the optimum temperature for egg development, when regarded as the temperature with highest hatchability was found to be 10°C. In conclusion, this study has shown that growth and the life‐history traits, egg developmental time and hatchability, of A. lusitanicus are highly influenced by temperature. However, data also show that temperatures within the range 2–20°C did not influence survival rates to any large degree, and that A. lusitanicus can quickly adjust to changes in temperature. The study provides a number of basic parameters which contribute to the understanding of the population dynamics of A. lusitanicus.